Gambaran Pola Asuh Ibu dengan Balita Stunting dan Tidak Stunting di Kelurahan Tengah, Kecamatan Kramat Jati, DKI Jakarta - Aisyah, Hira Fitriani (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2021)
Background. East Jakarta region has become the primary location of stunting, one of which is Tengah Village. Based on the weighing and preliminary data, the prevalence of stunting in 6 Posyandu in the two selected RWs reached 25.9%. Objective to find out the comparison of parenting patterns of stunting toddlers and non-stunting toddlers in Tengah Urban-Village, Kramat Jati Sub-District Method. This research is qualitative, with a case-study approach and collected through in-depth online interviews. The sample was selected by purposive sampling, based on the inclusion and exclusion criteria which 12 main informants had stunting and not stunting toddlers aged 24-59 months and key informants consisting of Nutrition Workers in the Puskesmas Tengah and Posyandu cadres. Results. The research results on key informants with stunting toddlers show that most mothers didn’t give exclusive breastfeeding to their children, provide food with less frequency, food variations are not varied because children are given a lot of snacks. Mothers with stunting toddlers also experienced low psychosocial support and low participation in Posyandu. Conclusion. There is a difference between mothers with stunting toddlers' parenting patterns and mothers with non-stunting toddlers.